Quantification of plasma levels of antiviral drug sofosbuvir and its metabolite GS331007 in patients of chronic hepatitis C with chronic kidney disease using UPLC-MS/MS method - Singhala, Ruchi; Tiwaria, Pramil; Dusejab, Ajay; Ramachandranc, Raja; Patiald, Ajay; Attrid, Savita (Asian Journal of Pharmaceutical Research and Development, 2020)
Sofosbuvir based regimens are the only treatment available in India and some other Asian countries for curing hepatitis C viral (HCV) infection. The main excretion route of sofosbuvir is renal so treatment of HCV infection is challenging in patients on hemodialysis. A simple and sensitive UPLC-MS/MS method was developed and validated according to USFDA guidelines on Linear Ion trap Quadrupole tandem mass spectrometer (QTRAP4500) which was applied to estimate the drug concentration of sofosbuvir and its metabolite GS331007 in patients of chronic kidney disease with HCV infection. Clopidogrel was used as internal standard (IS) for this study. All analytes and IS were separated on UPLC C18-HSS column (2.1mmX50mm, 1.7μm) with retention time of 2.07, 0.29 and 1.58 min, respectively, by using mobile phases of 5mM ammonium acetate in 0.2% formic acid in water (A) and 5mM ammonium acetate in 0.2% formic acid in methanol (B) on gradient elution mode at a flow rate of 0.6 mL/min. Calibration curve was plotted over the range of 10-200 μg/mL for both of the analytes and equation was calculated by applying linear regression method. Detections of daughter ions (sofosbuvir-530 to 243m/z, GS331007-261 to 112.1m/z and clopidogrel- 322 to 154.9m/z) were done in multiple reactions monitoring (MRM) mode and weights were analyzed by using Linear ion trap quadrupole mass spectrometer with turbo spray ion source. The developed method has been successfully used for quantification of drug concentration of sofosbuvir and GS331007 to see the safety of sofosbuvir in patients of HCV infection with renal failures.